Microfacies and Morphotectonic of the Tirgan Formation in Ghorogh Syncline (North of Chenaran) - Yavarmanesh, Hoda; Vaziri, Seyed Hamid; Aryaei, Ali Asghar; Jahani, Davood; Pourkermani, Mohsen (International Journal of Geography and Geology, 2017)
In this research, the Tirgan Formation in Ghorogh Syncline (north of Chenaran) with the thickness of 412 m in north flank and 251 m in south flank is studied. The Tirgan Formation in Ghorogh sectionsis included limestones, marlylimestones, shales and sandstones in lower parts of the formation. In these sections, there are impressions of echinoderms toxasteridae family, many of foraminifera from orbitolinidae family and also lots of calcareous algae that create facies variation along with other nonskeletal allochems. The study of sediment facies led to the recognition of four facies belts and six microscopic standard facies in the Tirgan Formation and shows the oscillation of sea level but totally it can be concluded that the basin was shallow and formed in the ramp platform. According to the evidence, the oolithic limestones and intercalated shales of the Tirgan Formation in south flank, Ghorogh Syncline are slided on the red sandstone of Shurijeh Formation as transition slides because of lubrication. These landslides are distinguished and formed (7times) because of the stresses which are done from the northern syncline to the south of Ghorogh valley and formed the current morphotectonic for the area. This phenomenon could name as decollement.